INTEGRASI PENDIDIKAN AGAMA ISLAM DALAM PEMBELAJARANBUDAYA ALAM MINANGKABAU DI SEKOLAH DASAR - Aziza meria (Universitas Islam Negeri Imam Bonjol Padang, 2017)
The general objective of this research is to find out the general picture of integration of Islamicreligious education in the learning of Minangkabau Nature Culture (BAM) in Elementary School(SD). While the specific purpose of this research is to know the integration of the value of faitheducation, sharia education, and moral education in BAM learning in elementary school. Thetype of research method used is field research (field research) that is by going directly to thefield to know the integration of values of Islamic education in learning BAM in elementary. Theapproach taken in data collection using qualitative methods, with techniques, observation,interviews and documentation. The data were obtained from several sources including PAIteachers, BAM teachers, students, principals, and parties related to the theme of this research.Further analyzed by descriptive and narrative analysis. The results of this research are: first, theintegration of PAI value in BAM learning in SD is the value of faith education. The value of faitheducation consisting of faith in God, to the Prophet, to the holy book of the Qur'an, and the finalday. Secondly, the value of sharia education is that of birth, marriage, and marriage ceremonies.Thirdly, the value of moral education is, about the matter of high upright raises the meaning ofmanners are the courtesy, the praiseworthy, the humble, the shyness and the lazy attitude whichcontradicts hard work.